Increasing Room Occupancy and Room Revenue through Price Decision Strategy - Ni Putu Evi Yuli Cahyani; I Ketut Astawa; Ni Nyoman Triyuni (International Journal of Glocal Tourism, 2020)
Purpose: The purpose of this article is to find out the pricing strategy implemented currently and the strategy should be implemented to increase room occupancy and room revenue at 5 star hotel in Kuta tourist area, Bali, Indonesia. Research methods: The data analysis techniques used in this research are quantitative analysis technique, analyzed using path analysis in SPSS Program version 25 and the qualitative descriptive analysis to interpret data information through word based on the result and the real situation. Findings: The pricing strategies implemented currently at the hotel are pricing strategy based on competitor, flexible pricing, and discount pricing. This strategy has a positive effect on room occupancy and room revenue. The flexible pricing is a profitable strategy to increase room occupancy and room revenue of the hotel. Implication: The hotel must pay attention to the prices offered by the competitors, the flexible prices offered by the hotel website, the discount priced offered to the customers and reconsider pricing strategies that have proven ineffective to be implemented in the future.